Cyclization enhances function of linear anti-arthritic peptides - Ali, Marina; Amon, Michael; Bender, Vera; Bolte, Andrea; Separovic, Frances; Benson, Heather; Manolios, Nicholas (Academic Press, 2014)
This study describes the biophysical and immunomodulatory features of a cyclic peptide termed C1 which consists of alternating d-, l-amino acids and is capable of inhibiting IL-2 production in vitro and reducing the induction and extent of T-cell mediated inflammation in animal models. Solid-state nuclear magnetic resonance demonstrates that the peptide orders the lipid bilayer, suggesting a transmembrane orientation, and this is supported by surface plasmon resonance indicating strong binding affinity of C1 to model membranes. In vitro cell viability and proliferation assays show that C1 does not disrupt the integrity of cell surface membranes. Permeation studies of C1 and analogs across human epidermis cells show that the stability and skin permeability are enhanced by cyclization. Treatment with C1 in an asthma and in an arthritis animal model resulted in a suppressed immune response. Cyclization may be a useful means of enhancing biological linear peptide activity and improving delivery.